Impact of bronchoalveolar lavage from influenza A virus diseased pigs on neutrophil functions and growth of co-infecting pathogenic bacteria - Lassnig, Simon; Hennig-Pauka, Isabel; Bonilla, Marta C.; Mörgelin, Matthias; Imker, Rabea; von Köckritz-Blickwede, Maren; de Buhr, Nicole (Frontiers in Immunology, 2024)
Influenza-A-viruses (IAV) infect the respiratory tract of mainly humans, poultry and pigs. Coinfections with pathogenic lung bacteria are a common event and contribute to the severity of disease progression. Neutrophils are a major cell type of the innate immune system and are rapidly recruited to the site of infection. They have several effector functions to fight invading pathogens, as the secretion of reactive oxygen species (ROS) or the release of neutrophil extracellular traps (NETs). NETs are known to promote the growth of Pasteurellaceae bacteria, especially if degraded by nucleases.In this study bronchoalveolar lavage fluid (BALF) from 45 field-infected pigs was analyzed for: 1. NET markers, 2. Influence on growth of lung bacteria and 3. Impact on neutrophil functions. BALF from 21 IAV-positive pigs and 24 lung diseased but IAV-negative pigs were compared.Here we show that neutrophils in lungs of IAV-positive pigs release vesicular NETs. Several NET markers were increased in the BALF of IAV-positive pigs compared to BALF from IAV-negative pigs. The amount of NET markers positively correlated with the viral load of the IAV infection. Interestingly, BALF of IAV-positive pigs enhanced the growth of bacteria belonging to the family of Pasteurellaceae as potential co-infecting bacteria. These effects were weaker with BALF derived from IAV-negative pigs with other lung infections. The intensity of oxidative burst in neutrophils was significantly decreased by BALF from IAV-positive pigs, indicating impaired antimicrobial activity of neutrophils. Finally, the lung milieu reflected by IAV-positive BALF does not enable neutrophils to kill Actinobacillus pleuropneumoniae, but rather enhances its growth.In summary, our data show that an IAV infection is affecting neutrophil functions, in particular the release of NETs and ROS. Furthermore, IAV infection seems to provide growth enhancing factors for especially co-infecting Pasteurellaceae and reduces the killing efficieny of neutrophils.